2013
DOI: 10.1158/1535-7163.mct-12-0811
|View full text |Cite
|
Sign up to set email alerts
|

Bortezomib and SAHA Synergistically Induce ROS-Driven Caspase-Dependent Apoptosis of Nasopharyngeal Carcinoma and Block Replication of Epstein–Barr Virus

Abstract: A novel drug combination of a proteasome inhibitor, bortezomib, and a histone deacetylase inhibitor, suberoylanilide hydroxamic acid (SAHA), was tested in nasopharyngeal carcinoma (NPC), both in vitro and in vivo. Dose-response of different concentrations of bortezomib and SAHA on inhibition of cell proliferation of NPC was determined. Mechanisms of apoptosis and effects on lytic cycle activation of Epstein-Barr virus (EBV) were investigated. Combination of bortezomib and SAHA (bortezomib/SAHA) synergistically… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
100
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 76 publications
(107 citation statements)
references
References 39 publications
(73 reference statements)
7
100
0
Order By: Relevance
“…Existing drugs target the main signaling molecules or pathways altered by EBNA-1, notably p53/TP53, ubiquitin-and proteasome-dependent proteolysis, and the NF-κB pathway (40)(41)(42). Proteasome inhibitors that restore the presentation of EBNA-1-derived epitopes should be particularly useful in EBNA-1-associated MM, via the destruction of EBNA-1-expressing cells and subsequent reduction in EBNA-1 stimulation of clonal plasma cells (43)(44)(45). Proteasome inhibitors may also act directly on clonal plasma cells infected by EBV.…”
Section: Discussionmentioning
confidence: 99%
“…Existing drugs target the main signaling molecules or pathways altered by EBNA-1, notably p53/TP53, ubiquitin-and proteasome-dependent proteolysis, and the NF-κB pathway (40)(41)(42). Proteasome inhibitors that restore the presentation of EBNA-1-derived epitopes should be particularly useful in EBNA-1-associated MM, via the destruction of EBNA-1-expressing cells and subsequent reduction in EBNA-1 stimulation of clonal plasma cells (43)(44)(45). Proteasome inhibitors may also act directly on clonal plasma cells infected by EBV.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that proteasome inhibitor bortezomib and histone deacetylase inhibitors have synergistic interactions in a variety of malignancies [13,14]. Secondgeneration proteasome inhibitor CFZ has shown activity against bortezomib-resistant cells [7].…”
Section: Discussionmentioning
confidence: 99%
“…First-in-class proteasome inhibitor bortezomib and histone deacetylase inhibitors have been reported to have synergistic interactions in some solid tumors [13,14] and hematologic tumors [15,16]. CFZ is a second-generation irreversible proteasome inhibitor and has shown activity against bortezomibresistant cells, indicating that their mechanisms of action are not completely identical [7].…”
Section: Introductionmentioning
confidence: 99%
“…HONE1-EBV cells and Daudi cells (a B lymphoblast cell line) were maintained in RPMI 1640 medium supplemented with 10% fetal bovine serum (FBS) and 1% penicillinstreptomycin (P/S). HONE1-EBV cells were established by infecting EBVnegative HONE1 cells with enhanced green fluorescent protein (EGFP)-tagged EBV (strain Akata) (33)(34)(35). The cells were grown at 37°C in a 5% CO 2 incubator.…”
Section: Methodsmentioning
confidence: 99%